CARACTERISTIQUES EPIDEMIOLOGIQUES ET CLINIQUES DES ENVENIMATIONS PAR LES INSECTES HYMENOPTERES AU MAROC EPIDEMIOLOGICAL AND CLINICAL CHARACTERISTICS OF THE ENVENOMATIONS CAUSED BY HYMENOPTERA INSECTS IN MOROCCO - Hajar, Rebgui; Hinde, Hami; Rachida, Soulaymani-Bencheikh; Nasma, Nekkal; Abdelmajid, Soulaymani; Faiçal, El Hattimy; Abdelghani, Mokhtari (European Scientific Journal, ESJ, 2013)
In order to reduce the morbidity of envenomations caused by Hymenoptera insects in Morocco, this study evaluates the incidence of those cases in the regions that have been affected by this type of poisoning and describes the epidemiological and clinical characteristics of the poisoned patients. A descriptive retrospective analysis was conducted on 175 cases of envenomation. Data was collected from two sources, the Toxico-monotoring systems and toxicological information, both based on suspected or proven data from The Moroccan Poison Control and Drug Monitoring Center (CAPM) from the 1 January 2008 to 31 December 2011. Entry and statistical analysis were done using Epi Info 2002. According to the results, the region of Tangier-Tetouan has recorded the highest number of poisoned patients (67 cases) with an incidence of 0.0062 per 100 000 inhabitants. The average age of the poisoned population was 21,6±16,9. Male patients were the most affected with 66% of cases (sex ratio (M / F) = 2). Hymenoptera insect bites have occurred most often in urban areas (62% of cases). There was a peak in bites during July, which corresponds to the period of the proliferation of insects (bees-ants...). 75.4% of patients were symptomatic. The most frequent clinical signs were local edema (25.9%), pruritus (20.5%) and localized pain (18.3%). The evolution was favorable in 81% of cases, 2 cases (1%) with had ongoing sequels and no cases of death were recorded. By studying these 175 cases of envenomation caused by Hymenoptera, we offers education and information to the Moroccan population, and an ecological knowledge about hymenopteran species involved, and the proper management of the poisoned for a better outcome.